Enhancing Electric Vehicle Performance: A Case Study on Advanced Motor Drive Systems, Integration, Efficiency, and Thermal Management - Ali Khan, Md. Yakub (Peneliti Teknologi Teknik Indonesia, 2025)
This paper presents a comprehensive review of advanced motor drive systems for next-generation electric vehicles (EVs), focusing on integration, efficiency, thermal management, and sustainability. As the automotive industry transitions towards electrification, the development of efficient motor drive systems is paramount to enhancing vehicle performance and sustainability. This study highlights the integration of various motor technologies, including permanent magnet synchronous motors (PMSMs), induction motors, and switch reluctance motors, with power electronics and thermal management solutions. Key findings reveal that utilizing advanced materials such as silicon carbide (SiC) and gallium nitride (GaN) in power electronics leads to significant improvements in energy efficiency and reduced energy losses. Effective thermal management strategies, including liquid cooling systems and advanced control algorithms, are critical for maintaining optimal operating conditions and enhancing overall system reliability. Furthermore, the paper discusses the sustainability implications of motor drive systems, addressing challenges related to material sourcing and environmental impact while highlighting the importance of recycling initiatives. As the automotive industry transitions towards electrification, the development of efficient motor drive systems becomes crucial for enhancing vehicle performance and environmental sustainability The insights gained from this case study underscore the potential of advanced motor drive systems to shape the future of electric mobility, promoting a more efficient and environmentally friendly transportation landscape. Overall, this research contributes valuable knowledge to the ongoing discourse on the development and implementation of next-generation motor drive technologies in the electric vehicle market.